Chronic Granulomatous Herpes Encephalitis in a Child with Clinically Intractable Epilepsy. (7th August 2012) - Hackney, James R.; Harrison, D. Keith; Rozzelle, Curtis; Kankirawatana, Suthida; Kankirawatana, Pongkiat; Palmer, Cheryl Ann
Abstract : Most patients with herpes simplex virus Type I encephalitis experience an acute, monophasic illness. Chronic encephalitis is much less common, and few late relapses are associated with intractable seizure disorders. A 10-year-old boy was admitted to our institution for intractable epilepsy as part of an evaluation for epilepsy surgery. His history was significant for herpes meningitis at age 4 months. At that time, he presented to an outside hospital with fever for three days, with acyclovir treatment beginning on day 4 of his 40-day hospital course. He later developed infantile spasms and ultimately a mixed seizure disorder. Video electroencephalogram showed a Lennox-Gastaut-type pattern with frequent right frontotemporal spikes. Imaging studies showed an abnormality in the right frontal operculum. Based on these findings, he underwent a right frontal lobectomy. Neuropathology demonstrated chronic granulomatous inflammation with focal necrosis and mineralizations. Scattered lymphocytes, microglial nodules and nonnecrotizing granulomas were present with multinucleated giant cells. Immunohistochemistry for herpes simplex virus showed focal immunoreactivity. After undergoing acyclovir therapy, he returned to baseline with decreased seizure frequency. This rare form of herpes encephalitis has only been reported in children, but the initial presentation of meningitis and the approximate 10-year-time interval in this case are unusual.